2020
DOI: 10.1101/2020.03.14.978676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Injectable Nanoelectrodes Enable Wireless Deep Brain Stimulation of Native Tissue in Freely Moving Mice

Abstract: Devices that electrically modulate the central nervous system have enabled important breakthroughs in the management of neurological and psychiatric disorders. Such devices typically have centimeter-scale dimensions, requiring surgical implantation and wired-in powering. Using smaller, remotely powered materials could lead to less invasive neuromodulation. Herein, we present injectable magnetoelectric nanoelectrodes that wirelessly transmit electrical signals to the brain in response to an external magnetic fi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The concept of using magnetoelectric nanoparticles (MENs) for brain stimulation was first proposed in 2012 [13] and was later demonstrated with MENs-mediated modulation of brain EEG activity [14] with the most recent attempt by Kozielski et al to demonstrate to enhance thalamic neuronal activity in vitro (preprinted) [15]. They used CoFe 2 O 4 -BaTiO 3 MENs due to their relatively strong magneto-electric (ME) effect owing to the strain-induced coupling between the magnetostrictive cobalt ferrite cores and piezoelectric barium titanate shells.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of using magnetoelectric nanoparticles (MENs) for brain stimulation was first proposed in 2012 [13] and was later demonstrated with MENs-mediated modulation of brain EEG activity [14] with the most recent attempt by Kozielski et al to demonstrate to enhance thalamic neuronal activity in vitro (preprinted) [15]. They used CoFe 2 O 4 -BaTiO 3 MENs due to their relatively strong magneto-electric (ME) effect owing to the strain-induced coupling between the magnetostrictive cobalt ferrite cores and piezoelectric barium titanate shells.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned results, originated with MENPs‐based studies on human cell lines as well as in vivo experiments on rodent models, support the MENPs' capability for noninvasive stimulation after delivery across the BBB, given the size of the nanoparticles ranges from 30 to 60 nm (Kozielski et al, 2020; Nguyen et al, 2021; Pardo et al, 2020). The experiments showed that MENPs were capable of stimulating the brain for at least 24 h after the administration in the brain.…”
Section: Menps For the Treatment Of Psychiatric And Neurodegenerative...mentioning
confidence: 78%
“…No data has been released yet using MENPs as nanocarriers for brain targeting in vivo. Though it is noteworthy that, as described above, recently MENPs were used for wireless activation of motor activity in mice (Kozielski et al, 2020). In this section, we speculate that the use of MENPs, as an innovative mechanism to externally control the targeted drug release, could be translated into a revolutionary new approach for the treatment of psychiatric and neurodegenerative disorders.…”
Section: Menps For the Treatment Of Psychiatric And Neurodegenerative...mentioning
confidence: 99%
See 2 more Smart Citations